Keterampilan Menulis Karya Ilmiah Tentang Inovasi Pengembangan Perpustakaan Bagi Pustakawan Sekolah - Dian Kristyanto; Yanuastrid Shintawati; Muh Sauqy; Elasa Yohana Titi; Tati Suarsi Lombu (Universitas Mercu Buana, 2022)
As a profession that is supported by science, librarians need to hone their scientific writing skills, one of the benefits derived from these skills is that it makes it easier for them to develop school libraries and become pioneers in moving literacy programs. The purpose of this community service is to guide school librarians in terms of writing scientific papers, especially those that specifically raise themes or issues regarding the development of school libraries. The method used is online-based socialization by emphasizes four main strategies including online seminars, online training, questions and answers, and group discussion forums. The results achieved in this activity were that the implementation was carried out in three sessions with different material topics related to writing scientific papers for school librarians. This Abdimas activity obtained several results, including the team succeeded in deciphering the skills of the participants related to scientific writing, unraveling phenomena that appeared in the school library from the activity participants, generating commitment from participants to produce scientific works, creating social media groups, and documenting activities. Keywords: librarian, school library, scientific work